THE COMMERCIALIZATION OF DA'WAH: AN ISLAMIC PERSPECTIVE - Dinda Ayu Pratiwi; Diniyah Khoerunnisa Alifiyah; Qinwan Nishrina Nurul Bayani; Raden Khayla Fadhilla Azzahra Firmansyah; Asep Rudi Nurjaman (Hunafa: Jurnal Studia Islamika)
The phenomenon of commercialization in Islamic preaching (da’wah) has become an increasingly relevant debate in the digital era. Social media platforms such as YouTube, Instagram, and TikTok provide vast opportunities for preachers to disseminate Islamic teachings, yet they also raise ethical dilemmas regarding the monetization of da’wah. This study aims to analyze the forms and strategies of da’wah commercialization and explore the Islamic perspective on this phenomenon. Using a qualitative approach and literature review method, this research examines relevant studies and Islamic preaching content on social media. The findings reveal that commercialization can positively impact da’wah by expanding its reach and sustainability. However, if not managed wisely, it may shift the essence of da’wah from spiritual goals to materialistic orientations. Therefore, clear ethical guidelines are necessary to ensure that digital da’wah practices remain grounded in Islamic values and maintain sincerity in conveying religious teachings